Impact of previous REnal TRansplantation on the mid-term renal Outcome after CARdiac surgery: the RETROCAR trial. Issue 2 (13th September 2022) - Beurton, Antoine; Fajardie, Antoine; Rubin, Sebastien; Belnou, Pierre; Aguerreche, Clement; Pernot, Mathieu; Mion, Stefano; Imbault, Julien; Ouattara, Alexandre
ABSTRACT: Background: Acute kidney injury (AKI) is one of the most common complications after cardiac surgery with cardiopulmonary bypass (CPB). Renal transplant recipients (RTRs) have a higher risk of cardiac surgery–associated AKI (CSA-AKI). A relationship has been strongly suggested between AKI and poor long-term graft survival. The main objective was to evaluate the impact of on-pump cardiac surgery on the 1-year renal allograft survival rate. Methods: The study population consisted of 37 RTRs and 56 non-RTRs who underwent cardiac surgery between 1 January 2010 and 31 December 2019. They were matched according to age, sex, preoperative glomerular function, diabetes and type of surgery. The primary composite outcome was renal survival, defined as patient survival without the requirement for permanent dialysis or new kidney transplantation at 1 year after surgery. Results: The renal survival rate was significantly lower in the RTR group than in the non-RTR group [81% versus 96%; odds ratio 0.16 (95% confidence interval 0.03–0.82), P = .03]. The proportion of patients who returned to permanent dialysis was higher in the RTR group than in the non-RTR group (12% versus 0%; P = .02). The proportion of patients with severe AKI was also higher in the RTR group. At 1 year after surgery, serum creatinine level, glomerular filtration rate and all-cause mortality rates were comparable between both groups. Conclusion: Patients with a functional renal allograft have a low 1-year renal allograft survival rate after cardiac surgery with CPB. In addition, these patients have significant risks of AKI and acute kidney disease after open-heart surgery. Graphical Abstract: